(untitled) (CIPEEX, 2024)
MASLOW WAS AN AMERICAN PSYCHOLOGIST WHO DESCRIBED A SET OF FIVE NEEDS LISTED IN A PYRAMID. EACH INDIVIDUAL REACTS DIFFERENTLY IN THEIR WORK ENVIRONMENT, MAKING MEETING THEIR NEEDS A PRIORITY. THE THEME OF THE STUDY DEVELOPED SOUGHT TO STUDY AND ANALYZE MASLOW’S THEORY AND ITS APPLICATION IN THE STUDY COMPANY, WITH THE AIM OF RESPONDING TO THE PROBLEM ARE THE HUMAN NEEDS EXPOSED BY MASLOW APPLIED BY THE COMPANY TEMA ENGENHARIA, IN ORDER TO ACHIEVE SELF-REALIZATION? THE JUSTIFICATION FOR DEVELOPING THIS WORK LIES IN THE NEED TO UNDERSTAND THE PRINCIPLES PRESENTED BY THE PSYCHOLOGIST, THEIR EVOLUTION AND APPLICABILITY FOR QUALITY BUSINESS MANAGEMENT. IN THIS SENSE, THE OBJECTIVE OF THE WORK IS TO UNDERSTAND AND STUDY THE CONCEPT OF MOTIVATION; DISCUSS THE THEORIES OF MASLOW AND HERZBERG; RELATE FIELD RESEARCH TO THE EXPOSED THEORIES. TO THIS END, THE DESCRIPTIVE METHOD, BIBLIOGRAPHICAL SURVEYS, FIELD RESEARCH WERE USED, WITH QUESTIONNAIRES CARRIED OUT VIA THE INTERNET WITH EMPLOYEES OF THE STUDY COMPANY; THUS, IT WAS POSSIBLE TO CONCLUDE THAT THERE IS NO REALITY IN THE COMPANY SIMILAR TO THAT PRESENTED BY MASLOW, AND ACTIONS ARE NECESSARY TO WORK THE MOTIVATION THEORY CORRECTLY.